Inclusive Education Based on Islamic Values: A Case Study at Madrasah Diniyah Takmiliyah Awaliyah Syamtalira Aron, North Aceh - Isnani, Fathin; Astuti, Dewi; Azdillah, Muhammad Rizky; Naeem, Ayesha Fakhar (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2025)
Inclusive education is a vital approach to ensuring equitable access to learning opportunities for all students, including those enrolled in non-formal Islamic educational institutions. Yet, the consistent role of Islamic Religious Education teachers in applying inclusive principles within madrasah diniyah remains insufficiently explored. This study adopts a qualitative methodology with a case study design, conducted at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Syamtalira Aron in North Aceh. Participants included asātiżah (teachers), santri (students), and institutional administrators, selected through purposive sampling. Data were gathered via in-depth interviews, non-participant observations, and document analysis, and analysed using the Miles, Huberman, and Saldaña model, comprising data condensation, data display, and conclusion drawing/verification. Credibility was ensured through triangulation of sources and methods. Findings indicate that teachers at MDTA Syamtalira Aron consistently implement inclusive education despite facing challenges such as limited infrastructure, insufficient training, and inconsistent parental support. Inclusive practices are evident in adaptive teaching strategies, personalized support for students with learning difficulties, and the integration of Islamic values—including tawhid (oneness of God), justice, compassion, brotherhood, and empathy. Inclusive education at MDTA not only improves access to learning but also contributes to students’ moral development and encourages teachers to enhance their professional competence. Conceptually, this study frames inclusive education from an Islamic perspective as a synthesis of pedagogical strategy and spiritual values. Practically, it offers a contextual implementation model for madrasah diniyah operating with limited resources.